PENGARUH MINAT DAN MOTIVASI PADA PENERAPAN MODEL DISKOVERI BERBANTUAN MEDIA ANIMASI TERHADAP HASIL BELAJAR FISIKA DI SMA NEGERI 4 KOTA BENGKULU - Yesy Oktalia; Indra Sakti; Dedy Hamdani (UNIB Press, 2017)
This research is aimed to find out the influence of learning interest in discovery learning model through animated-assisted media towards physics learning outcomes at SMA Negeri 4 Bengkulu, founding the influence between learning motivation in discovery learning with assisted-animated media on physics learning outcomes in SMA Negeri 4 Bengkulu, calculating the influence of learning interest of physics learning outcomes at SMA Negeri 4 Bengkulu, and calculating the number of learning motivation influence of physics learning in SMA Negeri 4 Bengkulu. This research is one group pretest-posttest design with respondents who are the students of class X MIPA 1 in SMA Negeri 4 Kota Bengkulu. The sample of this study was taken by using sampling purpusive technique which was obtained by 32 students of class X MIPA 1. Data retrieval using t-Test,the results obtained an average score interest in learning on learning outcomes is 3,02 tcal> t table 1,697 for a significant level of 95%.The results show that there is a significant influence of learning interest on the results of physics learning in SMA Negeri 4 Kota Bengkulu. Further, it is obtained the number of correlation coefficient which is 0.39. While the amount influence of interest in learning on physics learning results is obtained from the amount determinant which is 15%. For the influence of motivation on the result of physics learning obtained t-test result of mean score of motivation to result of learning is tcal 2,65> ttabel 1,697 for significant level 95%. The results showed that there is a significant influence of motivation on physics learning outcomes in SMA Negeri 4 Kota Bengkulu. Furthermore, it is got that the amount of correlation coefficient which is 0.39. While the influence numbers of interest in learning on physics learning results was obtained from a large determinant of 13.24%.